EFEKTIVITAS EXTRA VIRGIN COCONUT OIL DAN OLIVE OIL TERHADAP FUNGSI MEMORI DAN BELAJAR MENCIT - Gorga Menak Sihombing,* Rizna Tyrani Rumanti,** Decky Gunawan*** (NEURONA, 2019)
INTRODUCTION DEMENTIA IS A NEURODEGENERATIVE SYNDROME CAUSED BY CHRONIC PROGRESSIVE ABNORMALITY AND MULTIPLE MALFUNCTIONS OF THE NOBLE FUNCTIONS ESPECIALLY IN MEMORY AND LEARNING MEDIUM CHAIN TRIGLYCERIDES MCT AND POLYPHENOL IN EXTRA VIRGIN COCONUT OIL EVCO AND EXTRA VIRGIN OLIVE OIL EVOO CAN INCREASE COGNITIVE FUNCTION